تقييم دور جودة مستلزمات الإنتاج في خفض التكلفة الإنتاجية " دراسة ميدانيةعلى الشركة العامة للنسيج في محافظة اللاذقية - ديّوب محمد عباس; عمّار ابراهيم غسان (Latakia University Journal - Economic and Legal Sciences Series, 2014)
إن هدف كل شركة صناعية يتلخص في تطوير وتصنيع المنتجات التي تلائم حاجات الزبون النهائي مما يمكنها من تسويق تلك المنتجات بسعر مناسب يحقق لها عائداً مجزياً ،و يهدف البحث إلى إظهار أهمية اعتماد عامل الجودة في اقتناء مستلزمات الإنتاج من تجهيزات وآلات ومعدات ومواد أولية وبيان دورها الكبير في خفض التكلفة الإنتاجية , وجعل الشركة في موقع أفضل وضمان بقائها واستمرارها في عالم الأعمال كما تتمثل أهمية البحث من كونه يسعى إلى التعرف على طرق وأساليب الشراء على أرض الواقع،وسير الإنتاج فيها و التكاليف التي تتحملها هذه الشركات لاقتناء أفضل الآلات والمعدات والمواد الأولية , والتطرق لأهم المشاكل التي تعترضها, وكان من أهمّ النتائج التي تمّ التوصّل إليها: 1-يوجد أثر جوهريلجودة مستلزمات الإنتاجعلى التكلفة الإنتاجية . 2-يوجد أثر جوهري لتكاليف الجودة وتحسين العائد المالي . The goal of every industrial company is to develop and manufacture products that suit the needs of the final customer, enabling it to market those products at a reasonable and rewarding price. This research aims to show the importance of the adoption of the quality factor in the acquisition of production requirements for equipment and machinery, equipment and raw materials, and the statement of its significant role in reducing the cost of production, and to make the company in a better position and ensure its survival and continuity in the business world. The importance of this research also stems from the field study carried out by the researcher on public industrial companies and identify the ways and methods of purchasing, the conduct of their production, and the extent of the costs borne by these companies to acquire better production requirements of machinery and equipment and raw materials, and to address the main problems encountered. The most important results obtained show that: 1.There is a crucial impactof the quality ofproduction requirementson thecost of production. 2. There is a crucial impacton quality cost andthe improvementoffinancial returns.